Environmental Education and its importance in the conservation of endangered species (Research, Society and Development, 2020)
Environmental education comes to develop in the population a perception that it is the main protagonist when it comes to the conservation of biodiversity. Bats have an extensive diversity, are of great ecological importance, using insects and other arthropods, fruits, seeds, leaves, flowers, pollen, nectar, small vertebrates and blood as food, contributing to the dispersion of seeds and the control of insects, however, an erroneous perception of bats is portrayed. This work sought to demystify the prejudiced and erroneous concepts that people have about these mammals, promoting the awareness of elementary school students at Escola Estado da Paraíba. An exploratory class was held addressing the ecology of bats, and a questionnaire was applied to analyze the knowledge of the students and after the class, as well as a game was made “Tabuleiro dos Morcegos Brasileiros” where there were questions and challenges, which required participants to prior knowledge of bat ecology. It was verified by means of the second questionnaire that the explanations about the characteristics of bats and their relationship with the environment contributed for the children to stop having a misconception about bats. There is a lack of information regarding the importance of bats, these animals have a great role in nature, such as reforestation and pest control. However, they are still targets of prejudice and misinformation for many people.